The NLRP3 Inflammasome in Non-Alcoholic Fatty Liver Disease and Steatohepatitis: Therapeutic Targets and Treatment - Yu, Lili; Hong, Wei; Lu, Shen; Li, Yanrong; Guan, Yaya; Weng, Xiaogang; Feng, Zhiwei (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is one of the most prevalent liver diseases worldwide, and it can bloom a serial of serious condition, from simple steatosis, through non-alcoholic steatohepatitis (NASH), to fibrosis and ultimately cirrhosis and hepatocellular carcinoma. However, there is no approved pharmacotherapy. Recently, NLRP3 inflammasome as caspase-1 activation platform has been demonstrated to be critical for processing key pro-inflammatory cytokines and pyroptosis. The activation of NLPR3 inflammsome is a contributor to NAFLD development and in particular as a modulator of progression from benign hepatic steatosis to NASH. Various stimuli involved in NAFLD can activate NLRP3 inflammasome depending on the diverse cellular stresses that they cause. Meanwhile, the discovery of NLRP3 inflammasome-related blockers and medicines for treating NAFLD have support the therapeutic approach and positive effects in experimental models and clinical studies. In this review, we will discuss the activation, biological functions and treatment of NLRP3 inflammasomes in the context of NAFLD progression. Specifically, we focus on the different kinds of therapeutic agents involved in inhibiting NLRP3 inflammasome and summarize their pharmacological effectiveness for NAFLD treatment.